The development of an interactive mathematics app for mobile learning - Figueiredo, Mauro (2017)
Low achievement in mathematics education has been an increasing problem in the recent years in some countries. According to a 2010 study from the U.S. Department of Education, blended learning classes produce statistically better results than their face-to-face. There is also an increasing number of students using smartphones and tablets in schools. Mobile devices gained popularity as an educational tool and there are many schools that use them frequently in educational activities to improve learning. In this paper, we present the development of an application for smartphones and tablets to provide activities that students can do outside the classroom or at home and increase the time they spend learning and practicing mathematics. With this app students solve mathematic activities and are helped by the presentation of videos with the problems resolutions.